The grace of the Italian Renaissance - Mac Carthy, Ita (Princeton University Press, 2020)
"This book explores grace as a complex idea and term that at once expresses and connects the most pressing ethical, social, and aesthetic debates of the Italian Renaissance. Grace surfaced time and again in the period's discussions of the individual pursuit of the good life and in the collective quest to determine the best means to a harmonious society. It rose to prominence in theological debates about the soul's salvation and in secular debates about how best to live at court. It was absolutely central to the thinking of Reformation figures such as Erasmus and Luther, and just as central to the Counter-Reformation response. It played a pivotal role in the humanist campaign to develop a shared literary language and it featured prominently in the efforts of writers and artists to express the full potential of mankind. Grace abounded in the Italian Renaissance, yet it was as hard to define as it was ever-present. The courtier and writer, Baldassare Castiglione, for example, described it as that 'certain air' which distinguished excellent courtiers and court ladies from their mediocre counterparts, while his artist friend, Raffaello Sanzio (Raphael), saw it as that quality produced when one conceals the hard work and effort of art behind a veil of nonchalance and ease. This classically-inspired grace was used by many as a way of claiming distinction for themselves and of arguing for the pre-eminence of their chosen disciplines, but it drew criticism too from those who saw it as self-interested and superficial. Quarrels about the meaning and value of grace involved theologians, artists, writers and philosophers and intersected with the most famous debates of the time about language, society and the role of literature and the visual arts. As well as shedding light on what grace meant to those who invoked it, this book aims to trace the interdisciplinary transactions that the word made possible. Each chapter combines consideration of pivotal texts and images with interdisciplinary approaches, examining what grace meant to protagonists of the Italian Renaissance and exploring the correspondence, whether direct or indirect, between them. What emerges is a network of friendships, rivalries, agreements and disputes: a sketch of the interconnections that made the Italian Renaissance"--